Analysis of Saliva Samples from Oncological Patients Treated with 5-Fluorouracil and Leucovorin Calcium by Scanning Electron Microscopy with Energy Dispersive System - Mazzeo, Marcelo Adrián (2013)
This work presents a chemical and morphological analysis of samples of saliva taken from patients who were under treatment with intravenous chemotherapy with 5-fluorouracil and leucovorin calcium. Samples of saliva were extracted from fifteen patients during the three stages of the treatment: The initial stage (previous to the chemotherapy), the intermediate stage (during the chemotherapy), and the final stage (twenty-one days after finishing the treatment). An amount of 50 ll was collected in each visit. Chemical contrast images were taken by means of scanning electron microscopy, and X-ray characteristic spectra were obtained from all the studied samples by using an energy dispersive system from all the studied samples. Images that correspond to the intermediate stage showed important differences with respect to the initial and final stages. In addition, X-ray spectra provided information about the present elements in saliva and their relative abundance allowed us to determine variations in the chemical composition. The backscattered electron images and X-ray spectra from the intermediate stage showed clusters of crystals with fluorine content higher than those obtained in initial and final stages. This fact probably indicates the passage of metabolites of 5-fluorouracil and leucovorin calcium from the plasma to the oral cavity. This finding enhances the hypothesis proposed by other authors about the secondary effects of the drugs on the stomatognathic system such as oral mucositis, dysgeusia, and xerostomia with or without hyposalivation.